Ethical Issues In Medical Practice - Kibria, Golam (Journal of Bangladesh College of Physicians and Surgeons, 2014)
DOI: http://dx.doi.org/10.3329/jbcps.v31i3.20976 J Bangladesh Coll Phys Surg 2013; 31: 120-121